Kebijakan Pengentasan Kemiskinan melalui Program Keluarga Harapan di Kota Banjarbaru - Siti Rizayani; Syaharuddin Syaharuddin; Muhammad Rezky Noor Handy; Ersis Warmansyah Abbas; Jumriani Jumriani (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2022)
The acceleration of poverty alleviation in Banjarbaru City in the context of implementing policies in the field of social protection for the poor society is carried out through a hope family program (PKH). This program provides conditional assistance to the poor as social security to access health and education which includes health for toddlers and pregnant women as well as education for an early age. The government issues PKH to overcome poverty problems based on the number of poor households. This study aims to describe the impact of banjarbaru city government policies through PKH. The approach used was qualitative with descriptive method. The data was obtained by using interview, obsevation, and document studies. The results of the study showed that there has been an increase in various important sectors in the Banjarbaru city society through PKH, such as improvements in the economic, health, social and education fields. PKH is an economic policy that is able to improve the prosperity of the society in Banjarbaru city. Keywords: Governnment policy, poverty alleviation, Hope Family Program(PKH)